Financial crisis of 1931? British banking stability and the role of open-market operations - Matthias Römer (The Economic History Review, 2024)
To what extent was the summer of 1931 a financial crisis in Britain? Previous research has shown how London merchant banks were affected, but it remains unclear to what extent the largest commercial banks of London – the clearing banks – were under threat. Monthly balance sheets reported by clearing banks do not fully reflect the day-to-day liquidity in financial crisis, possibly overstating available liquidity. This article does not rely on what clearing banks reported, but what the largest five London clearing banks actually did on a daily basis during the summer of 1931. I find that the London clearing banks were not seriously under threat. This is because large-scale asset purchases by the Bank of England stabilized the liquidity of the London clearing banks. This intervention is consistent with previous crisis situations during the nineteenth century and at the outset of the First World War.
Keywords: 330; Bank of England; financial crisis 1931; open market operations; financial stability